Effect of land use on water yield from small agricultural watersheds of Western Ghats - Abdul Hakkim V M (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1993)
Effect of deforestation and other land use changes brought about by human activities of hydrologic cycle continues to be of great concern. A study was conducted to assess the effect of land use on water yield from small agricultural watersheds of Western Ghats of Kerala.